2010
DOI: 10.4321/s0004-06142010000400010
|View full text |Cite
|
Sign up to set email alerts
|

¿Divertículo uretral tras descenso anorectal asistido por laparoscopia (DARAL) en malformacion anorectal: es siempre necesario resecar el diverticulo?

Abstract: Resumen.-OBJETIVO: Con el uso cada vez mayor de la cirugía mínimamente invasiva, el divertículo uretral tras la cirugía anorectal se ha convertido en un problema. Los pocos casos descritos se han manejado con extirpación quirúrgica. Nosotros describimos un caso de divertículo uretral tras descenso anorectal asistido por laparoscopía (DARAL) con un resultado exitoso despues de un período de vigilancia activa. BIBLIOGRAFÍA y LECTURAS RECOMENDADAS (*lectura de interés y ** lectura fundamental)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There have been no complications from not closing the defect in any of our patients. There have been reports [5, 8, 10–12] describing the development of posterior urethral diverticula leading to compression and obstruction of the urethra as they increase in size. It was suggested that this complication occurred more often in laparoscopic procedures than in open PSARP.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no complications from not closing the defect in any of our patients. There have been reports [5, 8, 10–12] describing the development of posterior urethral diverticula leading to compression and obstruction of the urethra as they increase in size. It was suggested that this complication occurred more often in laparoscopic procedures than in open PSARP.…”
Section: Discussionmentioning
confidence: 99%